The institutional construction of firms - Richard Whitley (The University of Manchester, Manchester Business School, 2008)
The nature and economic role of legally constituted firms varies between market economies and changes over time. In particular, the governance of leading firms and how they develop distinctive organisational capabilities vary between institutional regimes and their supporting political-economic coalitions. These characteristics can be combined to distinguish five ideal types of firms that dominate different kinds of market economies. Institutions governing trust and authority relationships, state economic and legal policies, financial and labour markets and skill formation systems affect the development and change of dominant kinds of firms. Growing internationalisation of firms weakens national institutional influences on leading firm characteristics and strategies, especially their constraint of short-term economic opportunism. However, domestic institutions remain critical influences on transnational authority sharing and whether MNCs develop transnational organisational capabilities.
Keywords: 330; institutions; firms; governance; organisational capabilities; trust and authority; state structures and policies; financial and labour systems; internationalisation and MNCs; Marktstruktur; Globalisierung; Institutioneller Wandel; Theorie der Unternehmung